2020
DOI: 10.3390/ma13092175
|View full text |Cite
|
Sign up to set email alerts
|

Giant Stress Impedance Magnetoelastic Sensors Employing Soft Magnetic Amorphous Ribbons

Abstract: Soft magnetic amorphous alloys obtained via rapid quenching techniques are widely employed in different technological fields such as magnetic field detection, bio labeling, non-contact positioning, etc. Among them, magnetoelastic applications stand out due to excellent mechanical properties exhibited by these alloys, resulting from their amorphous structure, namely, their high Young modulus and high tensile strength. In particular, the giant stress impedance (GSI) effect represents a powerful tool to develop h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Makhotkin et al reported the first ribbon-based alternating current magnetic sensor prototype in [11]. They introduced ribbon-based prototypes suitable for magnetic biosensing both in label-free and magnetic label detection regimes [12,13]. In the latter, the corrosion stability was very important and compositions with chromium or molybdenum [14][15][16] were considered to take account of the need for low or high corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…Makhotkin et al reported the first ribbon-based alternating current magnetic sensor prototype in [11]. They introduced ribbon-based prototypes suitable for magnetic biosensing both in label-free and magnetic label detection regimes [12,13]. In the latter, the corrosion stability was very important and compositions with chromium or molybdenum [14][15][16] were considered to take account of the need for low or high corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…The MI and SI are very promising for the creation of highly-sensitive detectors of various external physical parameters [13][14][15][16] that can be appropriate for different kinds of applications including biology and medicine [17][18][19]. Therefore, despite a rather long history of MI and SI effect investigation, the fundamentals related to these phenomena and the search for new MI and SI materials are still under the special attention of researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to investigate the temperature dependence of MI responses and their temperature stability [20,21]. It should be noted that MI sensitive elements very often consist of different kind of materials [16,17], having different electrical conductivity values and different thermal expansion coefficients. Therefore, a change in the temperature can result in the appearance or modification of the distribution of mechanical stresses in the MI element and change the output signal [22].…”
Section: Introductionmentioning
confidence: 99%
“…The SI effect is, thus, a new addition to a broad series of magnetomechanical effects [ 22 ], some of which were first observed in the first half of the nineteen century, and are researched to this day due to high sensitivity of various experimental sensors, which can be obtained in newly developed materials [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. The most known of the magnetomechanical effects are magnetostrictive and Villari effects [ 33 ], the latter leads to a change in magnetic permeability due to the mechanical stress, by inducing temporary magnetic anisotropy in stress direction [ 34 ].…”
Section: Introductionmentioning
confidence: 99%